Influence of Rose All Day Instagram Sales Promotion Message And Endorsement By Beauty Influencer on Followers Buying Intention - Jessica Aisyah Larasati; Daniel Susilo (Asosiasi Pendidikan Tinggi Ilmu Komuniasi (ASPIKOM) Wilayah Riau, 2021)
This research was conducted due to the widespread use of social media as a marketing tool in Indonesia. This phenomenon has led to a social media marketing strategy through Instagram, one of the social media platforms used by a local cosmetic company called Rose All Day Cosmetics. This study aimed to determine the effect of the attractiveness of sales promotion messages on Rose All Day Cosmetics' Instagram account and endorsement by beauty influencers on followers' buying intention. The theories used in this research were the Elaboration Likelihood Model, the attractiveness of promotional messages, endorsement, and purchase interest theory. This research was quantitative explanative research through an online survey distributed using the direct message feature on Instagram to 398 respondents previously determined by the Yamane formula. The data obtained were tested with multiple linear regression. The findings indicated that each variable significantly influences the followers' buying intention partially or simultaneously, with a simultaneous effect of as much as 51,3% impact degree. The company must continue to follow the development of influencers, especially in the realm of micro-influencers